Quinoa: "Tear of the sun" - Naranjo Vargas, Plutarco (Revista Universidad de Guayaquil, 1983)
According to our prominent philologist Miguel Moreno Mora, quinoa (which is not a Quichua word) etymologically means: "tear of the sun." What a beautiful name, what a poetic name for such a noble cereal! Why did the aborigines call this food "tear of the sun"? Let's go from etymology to mythology. Many of the primitive cultures, throughout the world and also on our Continent, developed myths and then religions called "solar". In Elias the sun was the supreme god or one of the main gods. According to a forgotten verse: "The Sun is life, light and heat" and for primitive man he was the beneficial god.